A Comparison of Religious Freedom Guarantees for Adherents of Local Religions Between Indonesia and Japan - Berlian Three Normayani Aruan; Tiara Amandini Fajriya; Melysa Eka Febriyanti; Nelly Magdalina Sarumaha (Journal of Indonesian Constitutional Law, 2024)
Every individual has the right to freedom of religion, one of the principles of human rights that cannot be revoked. This principle recognizes a person's freedom to choose or not choose a religion and to switch from one religion to another. This freedom of thought is part of human dignity that must be guaranteed unconditionally, including the right to worship and believe according to one's conscience and mind. The research method used normative legal research, based on literature analysis and legal principles as the primary data, using conceptual, comparative, and legislative approaches. In Japan, applying the belief system is often associated with cultural rituals, especially in festivals that are part of Shinto teachings. Although Japan is known as a modern and technologically advanced country, traditional values are still maintained and become attractive. The 1945 constitution of Indonesia does not prohibit proselytism like Greece. Still, the First Precept of Pancasila recognizes the existence of God Almighty, which means that everyone is obliged to respect the religion and beliefs of others.